2021
DOI: 10.1039/d1ta06228j
|View full text |Cite
|
Sign up to set email alerts
|

An all-organic symmetric battery based on a triquinoxalinylene derivative with different redox voltage active sites and a large conjugation system

Abstract: The large π-conjugated system and dense active sites in tribenzoquinoxaline-5,10-dione (3BQ) enable it to deliver excellent lithium storage performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 41 publications
0
23
0
Order By: Relevance
“…Energy density values are calculated by the integration area under the charge–discharge profile, and power density values are calculated by energy density/discharge time (in hour). e) The comparisons of specific capacity at different current density of TAPT with other symmetric all‐organic lithium‐ion batteries (PZDB, [3b] Li 4 DHTPA, [4c] PNZTA, [5b] Pl1, [24] BPPFs, [25] DB [4e] and 3BQ [26] (Table S8)).…”
Section: Resultsmentioning
confidence: 99%
“…Energy density values are calculated by the integration area under the charge–discharge profile, and power density values are calculated by energy density/discharge time (in hour). e) The comparisons of specific capacity at different current density of TAPT with other symmetric all‐organic lithium‐ion batteries (PZDB, [3b] Li 4 DHTPA, [4c] PNZTA, [5b] Pl1, [24] BPPFs, [25] DB [4e] and 3BQ [26] (Table S8)).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, PS4 showed better stability compared to other reported GPEs (Table S1). A comparison of the performance enhancement effects with different modification methods on LMBs (Table S2, Figures S11 and S13) reveals that different porous carbons and PS4 could reduce the dissolution rate of the active material; ,,, PS4 could also substantially improve cycling stability.…”
Section: Resultsmentioning
confidence: 99%
“…may match the redox potential needs in all-organic symmetric batteries. 17,25 Additionally, rationally increasing the loading of redox-active sites (or reducing the redox-inert units) has been proven to be a universal strategy to improve the theoretical capacity for both organic cathode and anode materials. [26][27][28][29] For instance, Chen et al reported a polymer with a high loading of redox-active groups (C=O and C=N), which exhibited an impressive specific capacity of 502.4 mA h g -1 at 0.05 C. 30 Moreover, methods used in organic half batteries, such as manipulating weak intermolecular or intramolecular interactions (π-π interactions, hydrogen bonds, ion-dipole interactions, etc.)…”
Section: Introductionmentioning
confidence: 99%